2018
DOI: 10.5897/ajar2018.13357
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the adoption of agricultural innovations on underutilized cereals: The case of finger millet among smallholder farmers in Kenya

Abstract: Agricultural innovation adoption is fundamental in increasing incomes and food output in developing countries. However, the factors that influence farmers' decisions to adopt innovations in underutilized crops are not well-documented. Underutilized crops like finger millet have been an alternative form of sustenance for resource-poor farmers especially in arid and semi-arid areas in Kenya. They are more nutritive and resilient to environmental extremes and harsh weather conditions than common crops like maize.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
2
8
1
Order By: Relevance
“…barn technology. This result contradicts the findings from previous studies, such asAinembabazi et al (2016);Asfaw and Neka (2017);Jerop et al (2018);Muriithi et al (2016) andYigezu et al (2018) who suggested that access to extension information positively influences technology adoption. However, this result can be explained based on the content of tobacco extension information.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…barn technology. This result contradicts the findings from previous studies, such asAinembabazi et al (2016);Asfaw and Neka (2017);Jerop et al (2018);Muriithi et al (2016) andYigezu et al (2018) who suggested that access to extension information positively influences technology adoption. However, this result can be explained based on the content of tobacco extension information.…”
contrasting
confidence: 99%
“…Thus, a decision to start using a new technology is only reached if its perceived utility outweighs that of an existing or alternative technology. The perceived utility cannot be directly measured, instead, it is assumed to be a direct function of the observed socio-economic and institutional variables (Jerop et al, 2018). The fact that the theory acknowledges that there are socio-economic and institutional constraints to adoption, makes it incredibly useful in studying the adoption of rocket barns.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Patriarchy is dominant in the study area, with a negligible number of females having decision-making powers. The disenfranchisement of females, as discovered in other PRA studies, also reflects their peripheral roles in decision-making in agricultural activities and their ongoing exclusion from social services such as training and agricultural extension services [50], despite their active participation in farming operations such as ploughing, weeding and harvesting.…”
Section: Discussion 41 Demographic Attributesmentioning
confidence: 81%
“…A low level of education has been identified as a significant factor leading to poor adoption of agricultural technologies and access to information in rural and smallholder farming communities. Interventions such as farmer training and provision of information have less impact on agriculture systems where farmers have low levels of literacy [50,53]. Farmers who have a higher level of literacy are likely to adopt improved technologies and improve their farming practices for higher crop productivity and have the potential to engage in more profitable markets or negotiate for better prices with service providers [50,54].…”
Section: Discussion 41 Demographic Attributesmentioning
confidence: 99%
“…The results concurred with several studies suggest that educated agriprenuers are alleged to have a higher capability to attain, infer and respond to information on available innovations. (Jerop et al, 2018) found that educated agriprenuers are more likely to access information and guidance from extension providers which influence their usage of innovations.…”
Section: Innovations Used In Sorghum Agrienterprisesmentioning
confidence: 99%